Solanum elaeagnifolium and S. rostratum as potential hosts of the tomato brown rugose fruit virus. - Maor Matzrafi; Jackline Abu-Nassar; Chen Klap; Meital Shtarkman; Elisheva Smith; Aviv Dombrovsky (PLoS ONE, 2023)
Invasive weeds cause significant crop yield and economic losses in agriculture. The highest indirect impact may be attributed to the role of invasive weeds as virus reservoirs within commercial growing areas. The new tobamovirus tomato brown rugose fruit virus (ToBRFV), first identified in the Middle East, overcame the Tm-22 resistance allele of cultivated tomato varieties and caused severe damage to crops. In this study, we determined the role of invasive weed species as potential hosts of ToBRFV and a mild strain of pepino mosaic virus (PepMV-IL). Of newly tested weed species, only the invasive species Solanum elaeagnifolium and S. rostratum, sap inoculated with ToBRFV, were susceptible to ToBRFV infection. S. rostratum was also susceptible to PepMV-IL infection. No phenotype was observed on ToBRFV-infected S. elaeagnifolium grown in the wild or following ToBRFV sap inoculation. S. rostratum plants inoculated with ToBRFV contained a high ToBRFV titer compared to ToBRFV-infected S. elaeagnifolium plants. Mixed infection with ToBRFV and PepMV-IL of S. rostratum plants, as well as S. nigrum plants (a known host of ToBRFV and PepMV), displayed synergism between the two viruses, manifested by increasing PepMV-IL levels. Additionally, when inoculated with either ToBRFV or PepMV-IL, disease symptoms were apparent in S. rostratum plants and the symptoms were exacerbated upon mixed infections with both viruses. In a bioassay, ToBRFV-inoculated S. elaeagnifolium, S. rostratum and S. nigrum plants infected tomato plants harboring the Tm-22 resistant allele with ToBRFV. The distribution and abundance of these Solanaceae species increase the risks of virus transmission between species.